Genetic, molecular and biochemical basis of auditory aging: lessons from experimental models - Cervantes, Blanca; Bermúdez-Muñoz, Jose M.; Ruiz-García, Carmen; Lassaletta, Luis; Contreras, Julio; Murillo-Cuesta, Silvia; Varela-Nieto, Isabel (Auditio, 2022)
Age-related hearing loss (ARHL) affects one in three people older than 65 years and is the most prevalent sensorineural deficit. This type of hearing loss precedes and accelerates the onset of cognitive impairment and is associated with an increased risk for neurodegenerative diseases such as dementia and Alzheimer disease. The onset and progression of ARHL is influenced by genetic factors, which are still poorly understood, and environmental factors, which in particular include exposure to excessive noise and ototoxic substances. At present, no effective drug treatments are available for ARHL prevention or treatment, and therefore research in this field is a priority. In the research field, animal models offer a crucial tool for i) identifying new genes associated with ARHL, ii) understanding the cellular and molecular basis of auditory ageing and iii) defining new therapeutic targets and evaluating candidate treatments.